Production of Hydrogen and Volatile Fatty Acid by Enterobacter sp T4384 Using Organic Waste Materials - Kim, Byung-Chun; Deshpande, Tushar R.; Chun, Jongsik; Yi, Sung Chul; Kim, Hyunook; Um, Youngsoon; Sang, Byoung-In (한국미생물·생명공학회, 2013)
In a study of hydrogen-producing bacteria, strain T4384 was isolated from rice field samples in the Republic of Korea. The isolate was identified as Enterobacter sp. T4384 by phylogenetic analysis of 16S rRNA and rpoB gene sequences. Enterobacter sp. T4384 grew at a temperature range of 10-45 degrees C and at an initial pH range of 4.5-9.5. Strain T4384 produced hydrogen at 0-6% NaCl by using glucose, fructose, and mannose. In serum bottle cultures using a complete medium, Enterobacter sp. T4384 produced 1,098 ml/l H-2, 4.0 g/l ethanol, and 1.0 g/l acetic acid. In a pH-regulated jar fermenter culture with the biogas removed, 2,202 ml/l H-2, 6.2 g/l ethanol, and 1.0 g/l acetic acid were produced, and the lag-phase time was 4.8 h. Strain T4384 metabolized the hydrolysate of organic waste for the production of hydrogen and volatile fatty acid. The strain T4384 produced 947 ml/l H-2, 3.2 g/l ethanol, and 0.2 g/l acetic acid from 6% (w/v) food waste hydrolysate; 738 ml/l H-2, 4.2 g/l ethanol, and 0.8 g/l acetic acid from Miscanthus sinensis hydrolysate; and 805 ml/l 112, 5.0 g/l ethanol, and 0.7 g/l acetic acid from Sorghum bicolor hydrolysate.